Cases of intervention refusal encountered by public health nurses in Japan and characteristics of their support- qualitative analysis of described mother-child and elderly cases - Reiko Okamoto; Misaki Kiya; Keiko Koide; Miho Tanaka; Masako Kageyama (BMC, 2022)
Abstract Background The purpose of this study is to clarify the actual situation of the cases and the characteristics of support, focusing on mothers and their children, and elderly persons among the cases of intervention refusal encountered by public health nurses (PHNs) in Japan. Methods The data were descriptions of intervention refusal cases that were freely described by PHNs working for prefectural and municipal governments in questionnaire surveys nationwide. The characteristics of the cases and the support were categorized according to the situation of the case, and the number of descriptions was summarized and interpreted. Results The results revealed that interventions involving mothers and children were refused in most of by mother or parents. The refusals were related to child abuse, parental mental illness, obsessiveness, and complex backgrounds. The actual status of intervention refusal in elderly persons, interventions are frequently refused by elderly persons themselves in the case of self-neglect and by family members living with the elderly in the case of abuse. The refusals were related to mental disorders or dementia and living alone. In both cases, PHNs provided support in collaboration with multi-disciplinary and multi-agencies, and attempts were made to alleviate the situation of refusal to intervene, from detecting cases through contact during home visits and in other settings, and by coordinating with appropriate team members as required. Conclusions It is suggested that PHNs need to acquire practical skills depending on the characteristics of the case to cope with critical situations throughout the process of engagement.